An Overview of Various Applications of Cadmium Carboxylate Coordination Polymers - Gina Vasile Scaeteanu; Catalin Maxim; Mihaela Badea; Rodica Olar (Molecules, 2024)
This review highlights the most recent applications of Cd(II)-carboxylate-based coordination polymers (Cd(II)-CBCPs), such as sensors, catalysts, and storage materials, in comparison with those of Zn(II) counterparts. A wide range of species with luminescence properties were designed by using proper organic fluorophores, especially a carboxylate bridging ligand combined with an ancillary N-donor species, both with a rigid structure. These characteristics, combined with the arrangement in Cd(II)-CBCPs’ structure and the intermolecular interaction, enable the sensing behavior of a plethora of various inorganic and organic pollutants. In addition, the Lewis acid behavior of Cd(II) was investigated either in developing valuable heterogeneous catalysts in acetalization, cyanosilylation, Henry or Strecker reactions, Knoevenagel condensation, or dyes or drug elimination from wastewater through photocatalysis. Furthermore, the pores structure of such derivatives induced the ability of some species to store gases or toxic dyes. Applications such as in herbicides, antibacterials, and electronic devices are also described together with their ability to generate nano-CdO species.